HUBUNGAN USIA, PARITAS, DAN PENDIDIKAN TERAKHIR IBU HAMIL TERHADAP KESIAPAN MENGHADAPI PERSALINAN - delvira andini; Nina Sri (Jurnal Kesehatan Abdurrahman, 2026)
Maternal readiness to face the birthing process is a condition where the pregnant mother is ready physically, mentally, socially, and has sufficient knowledge to go through the birthing process. This readiness includes the mother's ability to recognize the signs of labor, prepare mentally, and arrange the necessary support and logistical needs. Mothers who are ready will be calmer, quicker in making decisions, and tend to experience a safer birth with less risk of complications. The aim is to determine the relationship between age, parity and last education of pregnant women on their readiness to face childbirth at TPMB Mukarti, A.Md.Keb. Where the variables studied are measured at the same time using a cross-sectional research design. The research results were based on the results of the Chi Square Test, the age variable obtained a p-value (0.045) < α (0.05), the parity variable obtained a p-value (0.004) < α (0.05) and the education variable obtained a p-value (0.003) < α (0.05). It was concluded that there was a significant relationship between age, parity and education on readiness for childbirth.